Estrategias regionales de desarrollo (ERD) y transformación digital pública: desarrollo de herramientas de apoyo para la evaluación de futuros escenarios de cambio climático en la Patagonia chilena - (:unkn) unknown (My University, 2025)
Although the projections for the XXI century shown a relatively moderate warming in Patagonia compared to other regions, the changes in air and sea surface temperature (increase) and precipitation (decrease) (Falvey & Garreaud 2009, Boisier et al. 2018) are already causing significant impacts on marine and terrestrial socio-ecological systems, including glacier retrieve, increase frequency and intensity harmful algal blooms, freshening of coastal waters, ocean acidification, changes in streamflow volumes, decrease or migration of fishing stocks, among others (MMA 2017). Ali these threats can be incorporated into a modelling framework that can help us to understand the complex feedbacks between a changing environment, economic productivity and human wellbeing. This approach can substantially contribute to anticipate and reduce the negative impacts of anthropogenic climate change in Chile through successfully applied adaptive actions. This research and development proposal aims to support regional governance and decision making processes through the development, validation and transfer of a technological solutions to assess and communicate potential impacts of future scenarios of climate change in the Chilean Patagonia, with an emphasis in marine socio-ecological systems. The successful development of this project and products is expected to promote informed decisión making regarding climate change adaptation within regional governments, the digital transformation of prospective scenario assessments carried out within the Regional Strategies of Development, and the future expansion of these tools to other regions in Chile and abroad.